Naming - Race, D.S.; Hillis, A.B. (Brain Mapping : An Encyclopedic Reference, 2015)
This current article summarizes the relationship between regions of the brain and cognitive processes involved in naming. In particular, we discuss regions involved in modal input, amodal semantics, lexical semantics, lexical access, phonology, and phonetics. There is a general consensus in the literature that naming (a) is generally dependent primarily on the left hemisphere, (b) is a complex task that involves the coordinated processing of multiple regions, and (c) is a task that can be disrupted by multiple types of brain injury, which can lead to different types of naming deficits.